A survey of robustness problems in quantitative model-based fault diagnosis - Patton, Ron John; Chen, Jie (Zielona Góra: Uniwersytet Zielonogórski)
Quantitative model-based fault diagnosis has become a popular issue in safety-critical systems, e.g., aircraft, spacecraft, chemical processes and nuclear plants. The use of dynamic system model information has been widely recognized as an important approach to fault detection and isolation for the case when there are no repeated hardware units. A prerequisite for reliability in model-based fault diagnosis is robust performance with respect to uncertainties.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka